Keluarga Berencana Perspektif Islam Dalam Bingkai Keindonesiaan - Fauzi, Al - (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2017)
Abstract: The conclusion of this study is in the perspective of Islamic law and keindonesiaan context of family planning, are permissible under certain conditions. This study proves that family planning has been deemed taboo and forbidden by religion was not to be but it can also be a thing that is recommended. This study agrees with some Muslim leaders like Quraish Shihab, Mahmud Syaltut, Imam al-Ghazali, Sheikh al-Hariri that allow the practice of birth control both in the realm of an individual (family) or social (community at large). This study rejects suggestions by some scholars as Madkour Professor of Islamic Law at the Faculty of Law and Abu Ala al-Mawdudi, who stated that the practice of birth control is forbidden by religion. This type of research in this paper is categorized as library research (library research) that is descriptive critical analysis using classical fikh science approachconcept}} maslahah. As for the source of the data in this study, there are two, namely primary and secondary data: the first primary data in this study is the Koran, the Hadith, the BKKBN. While secondary data is the source of the data obtained indirectly and able to complete the primary data in the form of books, scientific magazines, journals, and other data sources that support the completion of this writing..